PENGEMBANGAN KAPASITAS KAUM PEREMPUAN MELALUI COACHING FEMALEPRENEUR DI KABUPATEN TRENGGALEK - Habib Solehudin; Andriyanto Andriyanto; Zainiyah Alfirdaus (LPSDI Bina Patria, 2023)
This study purpose to determine the Capacity building of female community through coaching female on Trenggalek city. This research is including qualitative research under the case study approach. The data collection was done by doing the interview, observation, and documentation. The data analysis test used triangulation method by rechecking the credibility level of information. Entrepreneur to be implemented through female preneur program in order to capacity building with intensif choaching provide assistance that to designed in particular to give theoritis knowledge or practical in order are able to create superior human resources that able to independently and becomes female entrepreneur quality.